Synthesis, photochemical and photophysical properties of gallium and indium phthalocyanine derivatives - Chauke, Vongani Portia (Rhodes University, Faculty of Science, Department of Chemistry, 2008)
The syntheses of octasubstituted and unsusbstitituted Gallium(III) chloride and indium(III) chloride phthalocyanines (GaPc and InPc), their photophysical, photochemical and nonlinear optical parameters are hereby presented. The photocatalytic oxidation of 1-hexene using the synthesized GaPc and InPc complexes as well as electrochemical characterization is also presented in this thesis. Fluorescence quantum yields do not vary much among the four Ga complexes, except for complex 21c; therefore it was concluded that the effect of substituents is not significant among them. Solvents however, had an effect on the results. Lower Î¦[subscript F] values were obtained in low viscosity solvents like toluene, relative to highly viscous solvents, such as DMSO. The triplet quantum yields were found to be lower in DMSO than in DMF and toluene. The rate constants for fluorescence, intersystem crossing and internal conversion as well as fluorescence and triplet lifetimes are reported. Photodegradation and singlet oxygen quantum yields have also been reported. There was no clear correlation between the latter parameters. It was however established that the four gallium MPcs were stable, within the allowed stability range for phthalocyanines. High quantum yields of triplet state (Î¦[subscript T] ranging from 0.70 to 0.91 in dimethysulfoxide, DMSO) and singlet oxygen generation (Î¦[subscript greek capital letter delta], ranging from 0.61 to 0.79 in DMSO) were obtained. Short triplet lifetimes 50 to 60 Î¼s were obtained in DMSO). Calculated non-linear parameters of these complexes are compared with those of the corresponding GaPc derivatives and tetrasubstituted GaPc and InPc complexes. The optical limiting threshold intensity (I[subscript lim]) values for the InPc and GaPc derivatives were calculated and compared with those of corresponding tetrasubstituted InPc and GaPc complexes. The octasubstituted were found to be better optical limiters. Photocatalytic oxidation of 1-hexene by GaPc (21a-c) and InPc (22a-c) derivatives is also presented. The photocatalytic oxidation products for 1-hexene were 1,2- epoxyhexane and 1-hexen-3-ol. The % conversion values of 1-hexene and % selectivity of 1,2-epoxyhexane were generally higher for InPc derivatives. Even though InPc derivatives showed better photocatalytic results than GaPc derivatives, the former were less stable relative to the latter. Both type I and type II mechanism were implicated in the photocatalysis mechanism.
Keywords: Phthalocyanines; Photochemotherapy; Electrochemistry; Gallium; Indium